1994
DOI: 10.1093/infdis/169.4.746
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Causes Productive Infection of Macrophages in Primary Placental Cell Cultures

Abstract: To characterize the role of the placenta in vertical transmission of human immunodeficiency virus type 1 (HIV-1), the susceptibility of primary human placental cultures and of transformed trophoblast cell lines to infection by several HIV-1 isolates was examined. Placental cultures supported the replication of all strains tested, including lymphocyte-, macrophage-, and amphotropic isolates. All viruses replicated to modest levels, with production of both viral antigen and infectious virus in the culture supern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 43 publications
4
37
0
Order By: Relevance
“…Inconsistent results were also observed with HIV and varicella infection of trophoblasts (Douglas et al , 1992; Qureshi et al , 1996). HIV may infect the placenta and, subsequently, the fetus via placental macrophages, but not through trophoblasts, or through breaks in trophoblast integrity (McGann et al , 1994; Burton et al , 1996). Some viruses (HSV, adeno) may infect only less well-differentiated trophoblasts, with decreased infection once the cells differentiate into syncytiotrophoblasts (Parry et al , 1997a; Parry et al , 1997b).…”
Section: Viruses and Pregnancymentioning
confidence: 99%
“…Inconsistent results were also observed with HIV and varicella infection of trophoblasts (Douglas et al , 1992; Qureshi et al , 1996). HIV may infect the placenta and, subsequently, the fetus via placental macrophages, but not through trophoblasts, or through breaks in trophoblast integrity (McGann et al , 1994; Burton et al , 1996). Some viruses (HSV, adeno) may infect only less well-differentiated trophoblasts, with decreased infection once the cells differentiate into syncytiotrophoblasts (Parry et al , 1997a; Parry et al , 1997b).…”
Section: Viruses and Pregnancymentioning
confidence: 99%
“…HIV-1 genomic materials have been detected in placental macrophages (Hofbauer cells), cytotrophoblasts and syncytiotrophoblast. [10][11][12] HIV-1 replication and transmission through the placenta may occur through CD4-positive endothelial tissues or CD4-positive Hofbauer cells. Other findings concluded that placental macrophages form a barrier to primary HIV-1.…”
Section: Placental Overview: Pathophysiology and Immunologymentioning
confidence: 99%
“…In addition, HIV infection of pregnant women often results in poor outcome, including low birth weight babies, pre-term delivery, and an increased incidence of spontaneous abortions (D'Ubaldo et al, 1998;Kumar et al, 1995;Langston et al, 1995). Specific placental cell populations are permissive to productive HIV infection, probably contributing to transplacental transfer of virus or virus-infected cells across the placenta leading to fetal infection (David et al, 1992;McGann et al, 1994;Al-Harthi et al, 2002;Arias et al, 2003) . Although HIV infection clearly has the potential to negatively impact fetal and neonatal health, the mechanism and timing of HIV vertical transmission to the fetus is not yet clear.…”
Section: Introductionmentioning
confidence: 99%